Usability of Antivirus Tools in a Threat Detection Scenario - Körber, Michael; Kalysch, Anatoli; Massonne, Werner; Benenson, Zinaida (IFIP Advances in Information and Communication Technology, 2022)
Usability of antivirus (AV) tools has not received much attention yet. We conducted a laboratory study with 34 German students to investigate how they experience notifications and interventions of their AV when a threat is detected. During the study, a specifically designed harmless file triggered AV on participants’ laptops. Out of 34 participants, 19 users noticed AV messages, and 8 of them understood that the message communicated threat detection concerning a specific file. Moreover, only 6 users understood that this file was removed by the AV tool. Additionally, most participants were distracted by Windows OS messages that were unintelligible to them. We investigate reasons for incomprehension in our sample, and give recommendations for improved user interaction design of AV tools.
CRIS-Team Scopus Importer:2022-07-08